Personality change after stroke: some preliminary observations. Issue 12 (16th November 2004) - Stone, J; Townend, E; Kwan, J; Haga, K; Dennis, M S; Sharpe, M
Abstract : Objectives: To describe changes in personality after stroke and effects on carers. Methods: A consecutive series of patients was recruited from hospital admissions with stroke. A novel questionnaire was administered to the patients' main carer at nine months after the stroke to determine their perception of the patients' pre-stroke and post-stroke personality. Personality change was identified by changes in these ratings, and associations between personality change and the following variables explored: emotional disorder in patients and carers (measured using the hospital anxiety and depression scale and a structured psychiatric interview), stroke classification (Oxford community stroke classification), residual disability (Barthel index and Nottingham extended activities of daily living scale), and lesion characteristics on computed tomography (CT). Results: Carers of 35 patients with stroke took part. Reported changes in personality after stroke included: reduced patience and increased frustration (both p<0.0001, t test of difference), reduced confidence, more dissatisfaction, and a less easy going nature (all p<0.005). Occasionally, aspects of personality change were seen as positive by carers. There were relations between greater personality change and interviewer rated patient depression or anxiety (p<0.001) but not when this was self rated; and between personality change and both emotional disorder in carers (p<0.005) and greater disability (p<0.01) but not CT lesion characteristics. Conclusions: Carers commonly perceive personality change in stroke patients. This is associated with self rated emotional distress in the carer. More research is needed to understand what carers mean by "personality change" and what factors contribute to the perceived change.